Ultrasonically Assisted Decarboxylative Bromination of α, β-Unsaturated Carboxylic Acids Under Vilsmeier-Haack Conditions. Issue 5 (3rd May 2016) - Kumar, M. Satish; Rajanna, K. C.; Venkanna, P.; Venkateswarlu, M.; Sudhakar Chary, V.
Abstract : An efficient method for decarboxylative bromination of cinnamic acids (α, β-unsaturated carboxylic acids or 3-arylpropenoic acids) was achieved under relatively mild conditions using Vilsmeier-Haack reagent and KBr in acetonitrile media. Vilsmeier-Haack reagent is prepared by using 1:1 ratio of oxychloride (SOCl2 or POCl3 ) and DMF under chilled condition. Ultrasonically assisted reactions underwent smoothly with highly significant rate enhancements and afforded bromostyrenes as products in very good yields even though the reactions were too sluggish.